Evaluating antibiotic prophylaxis adherence: Implications for surgical site infections and wound care management - Velozo, Bruna Cristina [UNESP] (2024)
Aim: This study aimed to evaluate adherence to an antibiotic prophylaxis protocol and its impact on incidence of surgical site infection (SSI). Materials and method: A prospective observational cohort study was conducted at a teaching hospital in São Paulo, Brazil, from September to November 2015. The population were adults who underwent surgery with surgical antibiotic prophylaxis. The main outcomes measured were incidence of SSI at 30-days postoperatively, protocol adherence and surgical wound complications. STROBE guidelines were followed. Results: Among the 527 participants recruited, a 30-day follow-up was completed by 78.7 % (n = 415). Within this cohort, 57.6 % were females aged over 60 years (36.4 %). The incidence of SSI stood at 9.4 % (n = 39), with dehiscence being the most prevalent complication at 64.1 % (n = 25), followed by increased exudate at 51.3 % (n = 20). Notably, full adherence to the antibiotic prophylaxis protocol was low at 1.7 % (n = 7). The study observed a 60 % increased risk of SSI for every protocol mistake made. Alarmingly, 17.8 % (n = 74) of participants received antibiotic treatment exceeding the stipulated protocol duration. The overall mortality rate stood at 13.5 % (n = 56), with 1 % (n = 4) of these deaths attributed to SSI. Conclusion: There is a pressing global necessity to enhance antibiotic management, as underscored by this study's revelation of low adherence to the antibiotic prophylaxis protocol. This lack of adherence correlated with a notable incidence of SSI and subsequent wound complications. Nearly 20 % of participants received prolonged antibiotic treatment. Adhering strictly to the protocol could substantially impact SSI-related outcomes and enhance global antibiotic management.